ATTITUDE TO THE ISSUE OF VALENCY IN UZBEK LINGUISTICS - Mamarakhimov Sirojiddin Murtazaevich (Bright Mind Publishing, 2025)
The issue of valency in Uzbek linguistics is one of the significant processes in word and sentence structure, which has remained at the forefront of linguistic studies. Valency examines the syntactic and semantic properties of words, exploring how they connect with other words, specifically what arguments (actants) they require and the types of collocations they form. In the Uzbek language, the study of valency requires a deep analysis of both semantic transformations and syntactic structures of words. This article investigates the peculiarities of valency in Uzbek, focusing on the actants within word combinations and their roles, as well as the distinctive features of the valency system. The paper reviews scientific perspectives and theoretical approaches to valency in the Uzbek language, and through analyzed examples, demonstrates the practical application of the valency system in speech.
Keywords: Valency, Uzbek linguistics, syntactic structures, semantic properties, word combinations, actants, linguistic analysis, syntactic-semantic processes, grammatical system, theoretical approaches.